2023
DOI: 10.1021/acs.joc.3c01341
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Imidazo[1,2-a]pyridine-Fused 1,3-Benzodiazepine Derivatives with Anticancer Activity via a One-Pot Cascade GBB-3CR/Pd(II)-Catalyzed Azide-Isocyanide Coupling/Cyclization Process

Cheng-Ran Zhong,
Yang-Hong Zhang,
Gang Yao
et al.

Abstract: A new one-pot synthesis of imidazo[1,2-a]pyridine-fused 1,3-benzodiazepine derivatives via a sequential GBB-3CR/ Pd(II)-catalyzed azide-isocyanide coupling/cyclization process was developed. The Groebke−Blackburn−Bienayméthreecomponent reactions (GBB-3CR) of 2-aminopyridine, 2-azidobenzaldehydes, and isocyanides in the presence of a catalytic amount of p-toluenesulfonic acid gave azide intermediates without separation. The reaction was followed by using another molecule of isocyanides to produce imidazo[1,2-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, to the best of our knowledge, the metal-catalyzed C(sp 3 )-H bond functionalization of tertiary amines with one-step construction of heterocyclic skeleton has not been reported. Owing to our continuing interest in the synthesis of heterocycle by employing domino IMCRs [43][44][45][46][47][48], we wish to develop a novel one-step construction of 1,3,4-oxadiazoles using the copper-catalyzed oxidative Ugi/aza-Wittig reaction (Scheme 1, Equation ( 4)). In contrast to traditional organic synthesis, the process of functionalizing C(sp 3 )-H bonds through C-H bond activation has garnered considerable attention [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, the metal-catalyzed C(sp 3 )-H bond functionalization of tertiary amines with one-step construction of heterocyclic skeleton has not been reported. Owing to our continuing interest in the synthesis of heterocycle by employing domino IMCRs [43][44][45][46][47][48], we wish to develop a novel one-step construction of 1,3,4-oxadiazoles using the copper-catalyzed oxidative Ugi/aza-Wittig reaction (Scheme 1, Equation ( 4)). In contrast to traditional organic synthesis, the process of functionalizing C(sp 3 )-H bonds through C-H bond activation has garnered considerable attention [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated an undergraduate laboratory experiment wherein GBB-MCR-derived products were synthesized via in situ generated isocyanides from N -formylamines . The diverse fused heterocycles generated via GBB reaction include bicyclic imidazo­[1,2- a ]­pyridine, imidazo­[1,2- a ]­pyrimidine, imidazo­[1,2- a ]­pyrazine, imidazo­[2,1- b ]­thiazole, imidazo­[2,1- b ]­[1,3,4]­thiadiazole, imidazo­[1,2- b ]­[1,2,4]­triazole, imidazo­[1,2- b ]­pyrazol, and imidazo­[2,1- b ]­oxazole. Various polycyclic scaffolds (1–11, Figure ) are also synthesized via post modification of the GBB-derived products. , Recently, we demonstrated that the one-pot-derived GBB products can be elaborated to fused polycyclic heterocycles (12–14) involving Pictet–Spengler cyclization (Figure ). …”
Section: Introductionmentioning
confidence: 99%